Road to Tokyo 2020: has this atypical 5-year Olympic cycle represented an opportunity? - la Torre, A.; Vitale, J. A.; Codella, R.; Filipas, L. (The Journal of Sports Medicine and Physical Fitness, 2021)
In December 2019, a new coronavirus (SARS-CoV-2) was referred in Wuhan (Hubei, China) and it rapidly spread worldwide causing a severe respiratory infectious disease with fatal consequences in the worst cases. In March 2020, the World Health Organization declared the outbreak of a new coronavirus disease, named COVID -19, a pandemic with 135.646.617 confirmed cases of COVID-19-and 2.930.732 deaths (as of 13 April 2021). The global pandemic has created unique challenges for humans, and, during the first wave of COVID-19 outbreak, many Governments and national health authorities were forced to adopt containment and restrictive measures to limit further virus diffusion. As consequences of these "lockdown" policies and actions, manifold social and working activities were temporarily closed or prohibited including sporting events. [...] Games have been cancelled for medical issues and costing Japan 41.5 billion USD, based on operating expenses and loss of tourism activity. However, it is evident that the postponement in 2021 was an obvious choice from an epidemiological and healthcare point of view.